Susceptibility Study of Common Bacterial Isolates in Periprosthetic Joint Infection to Manually-mixed Fosfomycin Compared with Gentamicin Pre-mixed PMMA Bone Cement - Moonwong, MD, Songthai; Saengnipanthkul, MD, Sukit; Wongratanacheewin, PhD, Surasakdi (Journal of Southeast Asian Orthopaedics, 2022)
Objective: This study aimed to compare in vitro susceptibility of S. aureus and S. epidermidis, which are common isolates in periprosthetic joint infection, to manually-mixed fosfomycin with, the more commonly used, gentamicin pre-mixed bone cement. Materials and Methods: Modified disk diffusion technique was performed. Two clinical and 1 laboratory strains of S. aureus and 3 laboratory strains of S. epidermidis were cultured on agar plates. Manually-mixed fosfomycin (4 g fosfomycin in 40 g PMMA) and gentamicin pre-mixed (0.5 g gentamicin in 40.8 g PMMA) bone cement were prepared by using standard sterile mixing technique to produce 6 mm- spherical cement beads. The susceptibility of all bacteria on agar plates were tested against these cement beads. After incubation, the zone of inhibition was measured. Results: Disk diffusion susceptibility test demonstrated that all 3 strains of standardized S. aureus and S. epidermidis are more susceptible to manually-mixed fosfomycin cement beads than gentamicin pre-mixed beads as shown by the wider inhibition zone of each cement bead on agar plate. The mean difference of inhibition zone of both types of cement beads for S. aureus strain 1, 2 and 3 are 4.65 (3.24, 6.06), 17.33 (16.71, 17.94) and 9.44 (8.63, 10.25), for S. epidermidis strain 1, 2 and 3 are 12.39 (11.74, 13.03), 12.95 (12.93, 12.97) and 11.62 (11.26, 11.98), which are all statistically significant (p<0.01). Conclusions: The susceptibility of S. aureus and S. epidermidis to manually-mixed fosfomycin cement beads (4 g of fosfomycin in 40 g PMMA) are significantly more than to pre-mixed gentamicin beads (0.5 g gentamicin in 40.8 g PMMA) as demonstrated by in vitro disk diffusion study.